Tindak Pidana Pelaku Perzinahan Ditinjau Dalam Hukum Kriminologi yang Berlaku di Indonesia - Ramadhani, Prasya Putri; Yusuf, Hudy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Prostitution and sexual violence are complex issues with significant moral, legal, and social implications. In this context, public theology and criminology offer complementary perspectives for understanding and addressing these issues. Public theology provides a framework for exploring the ethical and spiritual dimensions of prostitution, as well as its impact on social relationships, while criminology researches the causes, consequences, and responses of the criminal justice system to crime. Through this approach, this article aims to reveal the relationship between adultery and criminal law in Indonesia, the sanctions that may be imposed on the perpetrators as well as how the understanding in responding to the issue of adultery and sexual violence. By doing so, it is hoped to generate deeper insights into social justice and legal certainty faced by the entire society. Adultery, Sexual violence, Public theology, Criminology, Criminal law, Adultery is a complex issue with significant moral, legal, and social implications. Adultery, which is often defined as sexual activity outside of marriage, can have a significant impact on family relationships and the social environment, as it involves any sexual act committed against someone’s will or without their consent. Both prostitution can have serious physical, emotional, and psychological consequences for victims and can have widespread social and cultural impacts.